Influence of Adhesives Storing Temperature on Adhesive Bond Strength - Muller, Miroslav (Manufacturing Technology Journal, 2014)
Adhesive bonds are very often applied in various climatic conditions and environments. Each environment is of specific properties which basically influence entire strength and reliability of an adhesive bond. The influence of the surroundings temperature on the strength and service life of the adhesive bond is one of the most important factors which has to be taken into regard by a designer when designing the bond. However, during a transit or a storing the adhesives can meet much higher or lower temperatures than it is recommended by a producer. The aim of the experimental part is a determination of the influence of the storing temperature in the interval -20 to 100 °C on the resultant strength of the adhesive bond. Two-component epoxy and acrylate adhesives which are used as the constructional ones were used for experiments. The subject of the research was the adhesives which are not specially determined for using in high or low temperatures. From the results it is obvious that the packing type is essential for a transfer of surroundings temperature into the adhesive. Higher storing temperatures (temperatures exceeding 60 °C) affect in a negative way the adhesive bond strength.
Keywords: adhesive bonding technology; packing; strength; surroundings temperature